1999
DOI: 10.1093/nar/27.14.2852
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine methylation transforms an E2F site in the retinoblastoma gene promoter into a binding site for the general repressor methylcytosine- binding protein 2 (MeCP2)

Abstract: The CpG-rich promoter of the retinoblastoma tumor suppressor gene (Rb-1) is normally unmethylated. However, aberrant methylation of CpG dinucleotides within the Rb-1 promoter has been depicted in certain tumors, which determines transcriptional inactivity of the gene and absence of the pRb retinoblastoma protein. Here we have concentrated on an E2F-binding site in the Rb-1 promoter. We show that the E2F site is required for cell-cycle regulated Rb-1 transcription in non-transformed cells. The function of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…(19,31). Additionally, our observation that pRb is bound to the cdc2, DHFR, and cyclin E promoters at the G 1 /S-phase boundary and during S phase is consistent with data showing increased Rb promoter activity at these same time points (14). Thus, we detected binding of pRb to the promoters of E2F target genes at a time when pRb protein is maximally abundant.…”
Section: Discussionsupporting
confidence: 91%
“…(19,31). Additionally, our observation that pRb is bound to the cdc2, DHFR, and cyclin E promoters at the G 1 /S-phase boundary and during S phase is consistent with data showing increased Rb promoter activity at these same time points (14). Thus, we detected binding of pRb to the promoters of E2F target genes at a time when pRb protein is maximally abundant.…”
Section: Discussionsupporting
confidence: 91%
“…One possibility is that CpG methylates the E2F binding sites, as this can affect DNA binding of E2F-1 and, at some promoters, also E2F-2 and E2F-3 (43,44). However, methylation is unlikely to account for the failure of E2F-1 to bind to the MYCN promoter for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…4). CpG methylation has been shown to prevent binding of E2F proteins to some E2F binding sites (43,44). Therefore, we pre-treated 1A3 cells with the DNA methyltransferase inhibitor 5-aC to remove repressive promoter-methylation prior to the addition of 4-OHT.…”
Section: E2f-1 Induces Ccne1 Expression and Apoptosis In Neuroblastommentioning
confidence: 99%
“…A methyl-CpG-dependent complex formed on the sequence MGMGGGAAAAA MG from the promoter of the retinoblastoma gene (Rb) (De Fiore et al 1999), has subsequently been shown by EMSA supershifts to include Kaiso (A. Prokhortchouk, unpubl.).…”
Section: Kaiso Is a Novel Methylated Dna Binding Protein Genes And Devementioning
confidence: 99%